A bibliometric and visualization analysis of research trends and hotspots on targeted therapy for breast cancer from 2003 to 2022 - Wu, Deqi; Pan, Chi; Hu, Yangying; Shi, Zhijie; Zhou, Yankun; Xiao, Min (Frontiers in Oncology, 2024)
Background: Breast cancer is a significant public health issue, exhibiting the most pronounced occurrence and fatality rates among malignant neoplasms globally. Targeted therapy is a medical intervention that focuses on specific molecular markers. This study aims to investigate and evaluate the current research trends and directions in the field of targeted therapy for breast cancer using bibliometric analysis. Method: The Web of Science database was utilized to retrieve relevant articles published between 2003 and 2022. The VOSviewer software and Bibliometrix package in the R language were employed to conduct co-occurrence and clustering analyses of authors, countries, institutions, journals, references, and the CiteSpace tool was utilized for keyword burst detection. Results: A total of 2,258 articles were included and the annual number of publications increased rapidly. The most prolific country on this topic was the USA (n=898, 39.77%) and the University of Texas MD Anderson Cancer Center published most papers (n=93). Dennis J. Slamon and Gabriel N. Hortobagyi stood out in the field, with Dennis J. Slamon leading in terms of co-citations(n=653) and Gabriel N. Hortobagyi topping the list in terms of published articles(n=18). The most productive journal was Breast Cancer Research and Treatment and the most cited journal was Journal of Clinical Oncology. The clustering of keywords indicated that the primary focus of researches in the past two decades was on the development and clinical evaluation of tumor-targeted drugs associated with the epidermal growth factor receptor (EGFR) family signaling pathway, and explored mechanisms related to biological behavior of breast cancer. Keywords co-occurrence and burst analysis identified current research hotspots and potential research trends. Conclusion: This study employed bibliometric analysis to examine research on targeted therapy for breast cancer over a span of 20 years, and identified development trends of research and elucidated potential research trajectories in the domain of this topic. This study helps in the identification of prospective collaborators and partner institutions for researchers.